Sistema integrado de monitoramento da saúde da criança na escola - Jean Andrade Canestri (2013)
The main goal of this dissertation was the design of a hardware/software system in order to monitor the development and health of children by collecting, integrating and organizing information related to socioeconomic data and biological parameters monitored at school. It consists of several subsystems (covering different hardware and software) of the acquisition, storage and transmission of data acquired through questionnaires, visual and auditory screening tests and analysis of reading performance. The visual screening includes testing of visual acuity, contrast sensitivity, stereopsis, color vision and phoria. Auditory screening evaluates the hearing threshold. The reading performance analysis is performed by an eye tracker, which measures the position of the eye at every moment. Basic biometric data, suchas weight and height, are also stored, which allows the monitoring of obesity and malnutrition in children. Socio-economic data is also collected, such as age of child, age of parents, family income and whether the family is in receipt of government social programs. With this system it is possible to monitor visual health, hearing health, obesity and malnutrition among children each year. After being aggregated and processed on a server, these data generate information to be made available to managers and public health education in the form of individual and group reports, could subsidize clinical, epidemiological and strategic conclusions and would be important in the formulation and monitoring of public policies in more predictive, preventive, efficient and coordinated way.